Improving Financial Reports by Revealing the Accuracy of Prior Estimates* - Hirst, D. Eric; Jackson, Kevin E.; Koonce, Lisa (Contemporary Accounting Research, 2003)
Abstract Several researchers (e.g., Lundholm 1999; Ryan 1997; Petroni, Ryan, and Wahlen 2000) have proposed a reporting mechanism to enhance the reliability of estimates and other forward‐looking information in financial reports. Their proposals require companies to report reconciliations of prior‐year estimates to actual realizations as supplemental information in their financial reports. Such disclosures would enable investors to distinguish between accurate and opportunistic reporting behavior, and, arguably, should create incentives for companies to estimate accurately in the first place. Our study provides evidence on these proposals. Specifically, we conduct two experiments within the context of an important intangible asset requiring estimation ‐ software development costs. Our results show that the proposed reporting mechanism is effective in communicating information about the accuracy of financial estimates. We find, however, that not all disclosures are equally useful. The most effective disclosures explicitly describe the implications of misestimation (if any) on both the balance sheet and on earnings, thereby reducing the computational complexity associated with less explicit disclosures. Furthermore, our results show that when the disclosures explicitly describe the implications of misestimation, investors reward accurate estimators but do not explicitly punish those who are inaccurate. We conclude that information about previous estimate accuracy is useful to investors and that regulators should consider the type of disclosure, because not all disclosures may be equally effective in creating management incentives for accurate estimation. Moreover, the competitive advantage conferred on firms that provide accurate estimates arguably should create incentives for all companies to estimate accurately in the future.